Properties of Aluminium-Ceramic Composite with Glassy Carbon as Solid Lubricant Designed for Automotive Applications / Właściwości Kompozytu Aluminiowo Ceramicznego Zawierajacego Węgiel Szklisty Jako Smar Stały Przeznaczonego Dla Motoryzacji - Posmyk A.; Myalski J.; Wistuba H. (Archives of Metallurgy and Materials, 2015)
The paper presents some basic information on manufacturing, structure and selected properties of a new hybrid composite with an aluminium alloy matrix elaborated for automotive applications. A porous oxide ceramics constitute the reinforcing phase of the composite and glassy carbon plays the role of a solid lubricant. The properties of a composite, which contains exclusively a ceramic reinforcing phase and a hybrid composite with porous ceramics and glassy carbon, have been compared. The composite with glassy carbon, obtained by the application of new method, features uniform carbon distribution upon ceramics walls which significantly influences its tribological properties. The friction in air coefficient of a hybrid composite sliding against grey cast iron is 0.12, whereas in the case of a composite containing exclusively ceramics sliding against cast iron it amounts to 0.3.